Upaya Guru Magang Dalam Menciptakan Suasana Belajar Kondusif Di Mi Plus Nur Rahma Kota Bengkulu - Sindi Lestari; Siska, Siska; An’nisa Wirayanti; Allisa Putri Lavnita; Nopriyani, Nopriyani (JPT : Jurnal Pendidikan Tematik, 2025)
This study examines the efforts of student teachers in creating a conducive learning environment at MI Plus Nur Rahma, Bengkulu City. A supportive classroom atmosphere plays a crucial role in ensuring effective learning, especially at the elementary school level where classroom management requires extra attention. Student teachers are expected to apply their pedagogical knowledge through practical strategies during the teaching process. This discussion highlights several key efforts, including establishing classroom agreements to build discipline, using ice-breaking activities to increase student focus and enthusiasm, utilizing various learning media such as projectors and speakers to enhance comprehension, and preparing student worksheets (LKPD) to support structured and independent learning. The results show that these strategies significantly improve student engagement, reduce classroom disruptions, and create a learning environment that is comfortable, active, and effective. These findings emphasize the importance of creativity and adaptability among student teachers in supporting the success of the learning process.